2011
DOI: 10.1111/j.1468-1293.2011.00969.x
|View full text |Cite
|
Sign up to set email alerts
|

Twenty‐four‐week efficacy and safety of switching virologically suppressed HIV‐1‐infected patients from nevirapine immediate release 200 mg twice daily to nevirapine extended release 400 mg once daily (TRANxITION)

Abstract: ObjectivesOnce-daily (qd) antiretroviral therapies improve convenience and adherence. If found to be effective, nevirapine extended release (NVP XR) will confer this benefit. The TRANxITION trial examined the efficacy and safety of switching virologically suppressed patients from NVP immediate release (NVP IR) 200 mg twice daily to NVP XR 400 mg qd. MethodsAn open-label, parallel-group, noninferiority, randomized (2:1 NVP XR:NVP IR) study was performed. Adult HIV-1-infected patients receiving NVP IR plus a fix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(48 citation statements)
references
References 14 publications
(12 reference statements)
2
46
0
Order By: Relevance
“…Because HIV-infected patients regularly visit our infectious diseases department every 1–3 months, we retrospectively screened all HIV-infected patients who were receiving NVP-IR-containing cART during the period from April 1, 2013 to June 30, 2013. Inclusion criteria for virological suppression were patients who were receiving NVP-IR plus two nucleos(t)ide reverse-transcriptase inhibitors, for a preceding minimum of 18 weeks, with undetectable (<50 HIV-1 RNA copies/mL) HIV-1 viral load (VL) in the previous 1–4 months [12]. Exclusion criteria were age < 18 years, pregnancy, or patients whose regimen included 400 mg NVP-IR once daily/switching from NVP-IR to NVP-XR/change of the NRTI backbone of combination regimens between July 1, 2013, and March 31, 2015.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because HIV-infected patients regularly visit our infectious diseases department every 1–3 months, we retrospectively screened all HIV-infected patients who were receiving NVP-IR-containing cART during the period from April 1, 2013 to June 30, 2013. Inclusion criteria for virological suppression were patients who were receiving NVP-IR plus two nucleos(t)ide reverse-transcriptase inhibitors, for a preceding minimum of 18 weeks, with undetectable (<50 HIV-1 RNA copies/mL) HIV-1 viral load (VL) in the previous 1–4 months [12]. Exclusion criteria were age < 18 years, pregnancy, or patients whose regimen included 400 mg NVP-IR once daily/switching from NVP-IR to NVP-XR/change of the NRTI backbone of combination regimens between July 1, 2013, and March 31, 2015.…”
Section: Methodsmentioning
confidence: 99%
“…To further simplify treatment regimens, a new extended-release (XR) formulation was developed [9, 10]. In phase III clinical trials, 400 mg NVP-XR once daily was found not inferior to 200 mg NVP-IR twice daily in terms of virological suppression in treatment-naïve patients (VERxVE study) [11] and in virologically suppressed patients who were switched from NVP-IR to NVP-XR (TRANxITION study) [12]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After adjustment for background therapy, the difference was 1.0% (95% CI: À4.3%-6.0%), indicating NVP-XR was noninferior to NVP-IR. 5 The proportion of patients experiencing division of AIDS (DAIDS) grade 3 or 4 events was similar in the NVP-XR and NVP-IR arms (3.7% vs 4.1%, respectively), although the number of patients reporting any AEs-whether or not defined as possibly drug-related by the treating physician-was greater in the NVP-XR than in the NVP-IR arm, perhaps because of the open-label study design. 5 The rates of AEs for 6 system organ classes that were greater in patients receiving NVP-XR at 24 weeks were followed up at 48 weeks ( Table 2).…”
mentioning
confidence: 95%
“…5 The proportion of patients experiencing division of AIDS (DAIDS) grade 3 or 4 events was similar in the NVP-XR and NVP-IR arms (3.7% vs 4.1%, respectively), although the number of patients reporting any AEs-whether or not defined as possibly drug-related by the treating physician-was greater in the NVP-XR than in the NVP-IR arm, perhaps because of the open-label study design. 5 The rates of AEs for 6 system organ classes that were greater in patients receiving NVP-XR at 24 weeks were followed up at 48 weeks ( Table 2). Note that the analysis of the differences in the rates of AEs was limited to AEs considered mild or moderate at 24 weeks because of the very low number of serious AEs in any category.…”
mentioning
confidence: 95%